Analysis of wastewater reuse potential in Beijing - Yang, Hong; Abbaspour, Karim C. (Desalination, 2007)
Increasing scarcity of freshwater resources and growing environmental awareness give rise to the use of reclaimed wastewater as an additional source of water supply. However, the amount of wastewater that can be reclaimed for reuse is subject to many factors, ranging from technical possibility to socio-economic and institutional conditions. Taking Beijing in China as a case study, this paper provides a systematic framework for the analysis of wastewater reuse potential under various driving forces and constraints. A linear programming model was used to analyse different reuse scenarios concerning alternative wastewater charges and reuse prices. The results suggest that the wastewater reuse potential is high at competitive prices. Wastewater treatment plants appear to be more economically efficient over on-site operation facilities in providing treated wastewater for reuse. The main users of the treated wastewater are agricultural irrigation and urban recreation sectors. The framework established in this study and the results of the Beijing case study help to better understand the complex systems and evaluate the effect of key factors influencing the potential of wastewater reuse. The study also provides a useful basis for the evaluation of wastewater reuse potential for other cities in China as well as cities in developing countries with similar conditions.